Pulmonary Hypertension and Hereditary Hemorrhagic Telangiectasia Related to an ACVRL1 Mutation - Yokokawa, Tetsuro (Intern Med, 2019)
Pulmonary hypertension and hereditary hemorrhagic telangiectasia (HHT) have an association mediated by activin A receptor type II-like 1 (ACVRL1) gene pathogenic variants. A 30-year-old woman was previously admitted to a hospital due to lung hemorrhage, and was diagnosed with pulmonary hypertension, but stopped follow-up visits. At 48 years of age, she was admitted to our hospital and was diagnosed with HHT. Genetic testing revealed an ACVRL1 pathogenic variant. After the initiation of pulmonary vasodilator treatment, the patient's mean pulmonary artery pressure started to decrease from 43 mmHg, declining to 37 mmHg when she was 58 years of age. This is the first report describing the 28-year follow-up of an HHT and pulmonary hypertension patient with an ACVRL1 mutation.